1998
DOI: 10.3109/13697139809080682
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal treatment and psychological function during the menopausal transition: An evaluation of the effects of conjugated estrogens/cyclic medroxyprogesterone acetate

Abstract: The use of hormones, given as a continuous estrogen and cyclic progestogen formulation after a formal calibration/run-in period, may have a beneficial effect on psychosocial distress experienced by women towards the end of their reproductive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…58 Three RCTs that assessed the secondary effects of HRT on anxiety symptoms in peri-and postmenopausal women reported little or no effects. [59][60][61] A large trial that randomized 419 postmenopausal women to 4 different HRT regimens found only modest effects of hormone treatments on anxiety scores after a long (up to 9 years) follow-up period. 62 However, these negative findings may be explained in part by a floor effect, because most study participants revealed relatively low anxiety scores at study entry.…”
Section: Managing Anxiety During Midlifementioning
confidence: 99%
“…58 Three RCTs that assessed the secondary effects of HRT on anxiety symptoms in peri-and postmenopausal women reported little or no effects. [59][60][61] A large trial that randomized 419 postmenopausal women to 4 different HRT regimens found only modest effects of hormone treatments on anxiety scores after a long (up to 9 years) follow-up period. 62 However, these negative findings may be explained in part by a floor effect, because most study participants revealed relatively low anxiety scores at study entry.…”
Section: Managing Anxiety During Midlifementioning
confidence: 99%
“…3 Potential benefits for this woman include improvement of menopausal symptoms, such as hot flashes, 6 sleep disturbances, [28][29][30] urogenital atrophy, 31,32 and possibly mood disorders. 28,[33][34][35][36][37][38] Evidence for improvement of hot flashes is based on a large number of randomized controlled trials of symptomatic women in their late 40s and early 50s. 6,39 Improvement in sleep disturbances [28][29][30] and urogenital atrophy 31,32 is supported by a fewer number of randomized controlled trials reporting a variety of measures.…”
Section: Patient 1: Initiating Therapy In a Perimenopausal Woman Withmentioning
confidence: 99%
“…Examples of such scales are the General Health Questionnaire 27,28 , the Hamilton Rating Scales of Clinical Anxiety and Depression 29,30 , the Beck Depression Index 27,28,31,32 , the Zung Anxiety Scale 33 and the Kellner-Sheffield Scale 33 . Examples of such scales are the General Health Questionnaire 27,28 , the Hamilton Rating Scales of Clinical Anxiety and Depression 29,30 , the Beck Depression Index 27,28,31,32 , the Zung Anxiety Scale 33 and the Kellner-Sheffield Scale 33 .…”
Section: Standardized Clinical Instruments As Dependent Variablesmentioning
confidence: 99%